Progress Report 2023: Decision Support System for WEFE Nexus to balance stakeholder priorities in sustainable land management - Verbist, Joren; Akramkhanov, Akmal (2023)
The present report is progress report prepared for describing about Decision Support System tool for WEFE Nexus in the Aral Sea basin. The tool is developed for generating innovative solutions that integrate the demands for water, energy, food, and ecosystems in the Aral Sea basin.